اشكالية القانون الدولي الإنساني التوازن الغائب و الدور المطلوب في تجارة و نزع التسلح (Revue El-Wahat pour les Recherches et les Etudes, 2017)
Jnternational Efforts Have Not Reached Satisfactory Results,Nor Have They Reached The Minimum Aspiration Of The Collective Security System Set Out In The Un Charter,States Are Still Seeking To Secure Their Own Security Or Even In Solidarity With Other Countries In The Form Of Alliances And Military Blocs In Both Cases Did Not Give Up The Weapon,Which Confirms That There Is A Doubt That The Possibility Of The Occurence Of Threats To Security If Not Security Is Already Violated So This Study Seeks To Show The Role Of International Efforts In The Application And Not In The Divorce Of International Law In Maintaining Security And Its Threats And Perhaps The Most Prominent Features These Threats Are Trade And Disarmament. Key Words - International Security- Collective Security – Crisis Of Cofidence – Security Guarantees – Nuclear Weapons.